Assessment of Healing Potential of Bombyx mori L. (Silkworm) Derivatives on Second-Degree Burns: Dose-Response and Combination Therapy Analysis - Evrydiki Katsikari; Alexandra Kyriaki; Andreas Vitsos; Margarita Vidali; Paschalis Harizanis; Ioannis Sfiniadakis; Maria Kostaki; Dimitra Ieronymaki; Asimina Terezaki; Georgios Ladopoulos; Chara Albani; Christina Barda; et al. (Medicines)
Background/Objectives: Burn injuries present significant treatment challenges due to the intricate nature of the healing process. Bombyx mori L. (silkworm) derivatives, containing healing-promoting proteins such as sericin and fibroin, as well as the anti-inflammatory enzyme serrapeptase, have shown promise as potential healing agents. This study aimed to identify the optimal dosage of silkworm body and gland extracts for burn healing, compare the selected dose’s effectiveness with that of silkworm cocoons, and assess the combined healing effects of a cocoon dressing and a silkworm body extract gel. Methods: An experimental model was employed using hairless SKH-hr2 female mice subjected to standardized second-degree burns. The mice received treatments with various formulations of silkworm body and gland extracts, silkworm cocoons, and a combined application of a cocoon dressing and silkworm body extract gel. Results: The most effective treatments were the cocoon dressing and the combination of cocoon dressing with 60% body extract gel. By Day 20, complete healing (100%) was observed in the 20% and 60% body and gland extract groups, while the cocoon and 60% gland extract groups exhibited 60% healing, significantly higher than the control group (0% healing). Wound contraction analysis showed the greatest reduction in surface area from Day 3 to Day 17 in the cocoon and 60% body extract groups (p < 0.05). Histopathological assessments revealed that the combination group exhibited the least tissue damage (score: 7), compared to the control (score: 10–13). Conclusions: The study highlights the poorly examined therapeutic potential of silkworm body and gland extracts, demonstrating their efficacy in accelerating burn healing. The effects observed by the silkworm cocoon and body extract suggests a novel and promising approach for burn wound management, warranting further clinical exploration.